Evolution of bodily distress disorders. Issue 5 (September 2020) - Basavarajappa, Chethan; Dahale, Ajit Bhalchandra; Desai, Geetha
Abstract : Purpose of review: The nomenclature and classification of somatoform disorders have undergone revisions in the fifth edition of the Diagnostic and Statistical Manual (DSM 5) and the upcoming eleventh edition of the International Classification of Diseases (ICD-11). The present review describes the changes that have evolved and highlight the possible challenges. Recent findings: Bodily distress disorders replace the term somatoform disorders. The emphasis on the symptoms to be medically unexplained has been removed. The need to have a certain number of symptoms associated with different organ systems has made way to the presence of one or more distressing bodily symptoms. The focus on psychological aspects like excessive attention, thoughts, and behaviors associated with bodily symptoms have been added to make it a more diagnosis of inclusion rather than exclusion. An additional qualifier of severity has been added, which highlights the importance of impairment associated with these symptoms. Summary: The diagnostic criteria for bodily distress disorders is a step towards making the diagnostic criteria clinically useful and appears to be applicable across the healthcare settings. However, the ability to discern this diagnosis with the newly revised classification of chronic pain and the possibility of over psychologizing the medical disorders need to be researched.